Comprehensive rehabilitation program after post-resistive hip arthroplasty of GMRS as a result of treatment of the aneurysm cyst of the femoral neck - Szczypiór-Piasecka, Karina; Siemińska, Julia; Antczak, Krzysztof; Mińko, Alicja (Journal of Education, Health and Sport, 2021)
Malignant bone cancer is rarely detected in its early stages and there is usually already soft tissue infiltration at diagnosis. Symptoms that occur include pain that worsens at night, tissue thickening, and limitation of limb mobility due to bone destruction. THE AIM OF THE STUDY was to describe a case of a patient after resection of a malignant bone tumor (Fibrolastic osteosarcoma) and to create a program of comprehensive postoperative rehabilitation. MATERIAL AND METHODS The case study presented in this study confirms the need for holistic treatment of a patient diagnosed with a malignant bone tumor. In patient A.S. at the age of 23, an aneurysmal cyst in the neck of the left femur was diagnosed with a pathological fracture and extensive bone destruction. Radical treatment with total post-resection arthroplasty was performed. Inpatient physiotherapy in the hospital and rehabilitation 5 months after the surgery have been described. The work confirms the necessity of a holistic application of the patient care process, which includes diagnostics, treatment and rehabilitation. RESULTS Physiotherapy is introduced the day after surgery and continues until the patient is discharged home. Physiotherapeutic methods and exercises are adapted to the scope of the operation, general condition and age of the patient. The goal is for the patient to achieve the greatest possible independence of movement and daily activities. In post-hospital rehabilitation, the goal is to restore the normal, achievable, mobility and stability of the joints. The patient should adopt the correct gait pattern with the minimum possible protection with orthopedic equipment. CONCLUSIONS 1. Patients after proximal femur resection and GMRS replacement surgery should begin rehabilitation on the first day after surgery. 2. Manual therapy and osteopathy are extremely important in the rehabilitation program after surgery to remove a bone tumor.